Direct Induction in Wild-Type NEUROSPORA CRASSA of Mutants (qa-1(C)) Constitutive for the Catabolism of Quinate and Shikimate - Partridge, C. W. H. (1972)
A color test has been developed for the selection and identification of mutants in Neurospora crassa, constitutive for the three normally inducible enzymes which convert quinate to protocatechuate. By this means seven such mutants have been recovered after ultra violet irradiation of wild type and have been shown to be allelic (or very closely linked) to the qa-1(C) mutants previously obtained by other means. Thus, the regulation of the synthesis of these three catabolic enzymes is indicated to be under the control of a single gene, qa-1(+).